Wednesday

July 23, 2014

July 23, 2014

Posted by **Anon** on Wednesday, September 4, 2013 at 9:05pm.

y=sin(x)*(sinx+cosx)

- Math -
**Steve**, Wednesday, September 4, 2013 at 11:16pmjust use the product rule

If y = uv then

y' = u'v + uv'

where u=sinx and v=sinx+cosx

y' = cosx(sinx+cosx) + sinx(cosx-sinx)

= sin2x + cos2x

**Related Questions**

calculus - Could someone check my reasoning? thanx Find the derivative of the ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Trigonometry - Prove the following trigonometric identities. please give a ...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...